(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The following research had the purpose of designing an inventory management system for the warehouse Técnitaller S.A. S of the city of Neiva; this due to the inefficient administration of its inventories which have generated reprocesses, shortages, obsolescence, low level of service, damage in merchandise among others; the methodology used corresponds to a non-experimental, transversal and descriptive study that begins with the diagnosis of the area, the elaboration of the proposal of inventory management and the economic analysis of the same one; As a result of the analysis it was determined that the model to be implemented in the company integrates an information system comprising 4 management modules (Purchasing, warehouse, inventories and dispatch), whose implementation value is 21,595,150. 595,150, which will be implemented by Word Office. The implementation of this system will allow the company to optimize inventory management which will be reflected in lower costs of maintaining inventory, ordering, storing and other variables.